Matel Organic Frameworks in Drug Delivery: Synthesis and Drug Loading Strategies - Wang Weifu (MATEC Web of Conferences)
Metal-organic frameworks (MOFs), are widely used in the field of biomedicine. This material display the capacity to change the structures. It can achieve the appropriate size of the apertures by changing the preparation conditions. MOFs have numerous benefits due to their inherent qualities. It can serve as a medication carrier and has several advantages. Among them, an important advantage of MOFs as drug delivery systems is their ability to load large amounts of drugs. Moreover, it is biocompatible to use MOFs as drug delivery carriers. Besides, it is also biodegradable so that the use of MOFs is environmental-friendly. Therefore, studying the application of MOFs in drug delivery systems is of great value. The synthesis method has a significant impact on the structure of MOFs. In this work, the synthesis of MOFs for drug delivery applications is the main topic of this article. The synthesis procedures are discussed in detail. In addition, the drug loading strategy of MOFs is also worth studying. This work also summarizes the drug delivery strategies of MOFs. The research of this work will contribute to the further development of MOFs as drug delivery systems.